Students will learn how the unit circle can be used to prove all of the following theorems:

- \(\cos(90^\circ - \theta) = \sin \theta\)
- \(\sin(90^\circ - \theta) = \cos \theta\)
- \(\cos(90^\circ + \theta) = -\sin \theta\)
- \(\sin(90^\circ + \theta) = \cos \theta\)
- \(\cos(180^\circ - \theta) = -\cos \theta\)
- \(\sin(180^\circ - \theta) = \sin \theta\)
- \(\cos(180^\circ + \theta) = -\cos \theta\)
- \(\sin(180^\circ + \theta) = -\sin \theta\)
- \(\cos(270^\circ - \theta) = -\sin \theta\)
- \(\sin(270^\circ - \theta) = -\cos \theta\)
- \(\cos(270^\circ + \theta) = \sin \theta\)
- \(\sin(270^\circ + \theta) = -\cos \theta\)